1996
DOI: 10.1007/bf02251069
|View full text |Cite
|
Sign up to set email alerts
|

The history and future of cross-cultural psychiatric services

Abstract: With cultural issues prominent in the United States today and with ongoing rapid changes in health care management and delivery, this paper discusses the shift from a genetic-type psychiatry (i.e., assuming that humans the world over are no different, and will react to given stressors in life in the same manner) to one recognizing that cultural beliefs, mores, peer pressure, family expectations, and other ingredients operate in unique combinations in various cultures and ethnic groups. These social and cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…These are consistent with other work which critiques the historical development of cross-cultural services and offer a model of service organization and development designed to meet the needs of ethnicminority families (Bhugra, 1999;Bhugra and Bahl, 1999;Moffic and Kinzie, 1996). Ethnocentric and particularly Eurocentric explanations of emotional and psycho-social development are not inclusive enough for the development of diverse ethnic-minority children.…”
Section: Multi-disciplinary Responses To Multi-cultural Needssupporting
confidence: 79%
“…These are consistent with other work which critiques the historical development of cross-cultural services and offer a model of service organization and development designed to meet the needs of ethnicminority families (Bhugra, 1999;Bhugra and Bahl, 1999;Moffic and Kinzie, 1996). Ethnocentric and particularly Eurocentric explanations of emotional and psycho-social development are not inclusive enough for the development of diverse ethnic-minority children.…”
Section: Multi-disciplinary Responses To Multi-cultural Needssupporting
confidence: 79%
“…These are consistent with other work which critiques the historical development of cross-cultural services and offer a model of service organization and development designed to meet the needs of ethnic minority families (Moffic and Kinzie, 1996;Bhugra, 1999;Bhugra and Bahl, 1999). Ethnocentric, and particularly Eurocentric explanations of emotional and psychosocial development are not inclusive enough to encompass the developments of diverse ethnic minority children.…”
Section: Components Of a Culturally Competent Practicesupporting
confidence: 77%
“…Those investigators found evidence of strong simultaneous belief in both systems. Other research on the effects of the penetration of the Western medical system into traditional societies indicates that with time, these two models eventually reach a level of acceptable integration (Beiser, 1985;Bilu & Witztum, 1994;Lewis-Fernandez & Kleinman, 1995;Kleinman, 1978;Kortmann, 1987;Moffic & Kinzie, 1996;Unschuld, 1976). However, given that acculturation is a lengthy process, it might be expected that full integration might encompass several generations.…”
Section: Cultural Contrasts In Explanatory Models For Mental Diseasementioning
confidence: 96%